Respuesta de plantas multiplicadas en cámaras térmicas de diferentes tipos de cormo para el establecimiento del cultivo de plátano (Musa AAB). - Jimmy Eladio Mendieta Tovar (2020)
In Ecuador, the establishment and renovation of commercial banana plantations in small and medium producers is increasing, obtaining healthy and good quality seeds is difficult, due to the high cost of in vitro plants. The objective of this research was: evaluate the agronomic response of banana plants cv Barraganete from corms multiplied in thermal chamber, was carried out in the EIA-Pichilingue of INIAP, located in the province of Los Ríos Km 5 via Empalme. Five cane beds were built 30 cm from the ground, filled with soil which were covered by plastic to increase the temperature using the thermal chamber method, where banana corms were established (5, 7 and 10 months), these were stimulated by making a cross-sectional view of the pseudostem at the height of the cross-shaped rhizome neck, to see the response of each of the established corms, the student t test was used, determining which type of corm presented the best results. The five-month corm recorded the lowest averages with 9 shoots and 6 plants, the seven-month corm obtained 11 shoots with a total of 27 plants per corm, the corm of plants in production (10 months of age) recorded the highest number of shoots per corm with 13 shoots and a total of 30 plants. Within the thermal chamber eight stimulations (one every fifteen days) were made and ten times second generation buds (one every fifteen days) were obtained, five plants were selected by obtaining and were established in the field, at the end of the vegetative stage it was possible to appreciate the plants both in height (m) with averages ranging from 1.2 to 2.1 as a circumference of the pseudo total (cm) with averages between 27 and 50. Keywords: Thermal chamber, cormo, stimulation, plants.